NUTRITIONAL COMPOSITION, HEALTH BENEFITS AND POTENTIAL APPLICATIONS OF BLUEBERRY: A COMPREHENSIVE REVIEW - ZAHRA, NASEEM; SAEED, MUHAMMAD KHALID; HAMID, HUFSAH; QAMAR, ABDULLAH; SAEED, ASMA (Innovare Journal of Agricultural Sciences, 2023)
Background: Blueberries are one of the most popular and nutritious fruits in the world. They are small, round, and blue with a sweet and tangy flavor. Blueberries are a good source of vitamins, minerals, and antioxidants, making them a healthy addition to any diet. Objective: This study is a review of the origin, taxonomy, classification, cultivation, commercial importance, and health benefits of blueberry. Methods: A wide range of electronic data was gathered including different articles, review papers. Conference papers, abstracts published in national and international proceedings, books, and thesis. The current research was based on International database such as Google Scholar, BIOSIS, Journal Citation Reports, Research Gate, Science Direct, and Scopus with particular keywords. Results: Blueberries are the best source of antioxidants, polyphenols, and fiber. Blueberries have very best nutritional aspects including neuro-protective, osteoprotective, reno-protective, and opthalmo-protective properties. Conclusion: Blueberries are native to North America and have been used by Native Americans for centuries for their medicinal properties. In recent years, blueberries have gained widespread popularity due to their many health benefits, including their ability to improve heart health, reduce inflammation, and improve cognitive function. In addition to their cardiovascular and anti-inflammatory benefits, blueberries may also have cognitive benefits.